Evaluasi Keberhasilan Pembangunan Ekonomi Di Provinsi Maluku Utara - Muhammad Cahyudi I Subur; Ida Nuraini (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
The purpose of this study is to determine the extent to which the success of economic development in North Maluku Province and the influence of population, investment and government expenditure on per capita income in North Maluku province. The method used in this study using panel data regression analysis method. The results of this study indicate that the level of development success achieved by North Maluku Province so far can be said to have progressed but is relatively slow. While the results of the panel data regression research show that partially, the Population and Government Expenditures have a positive and significant effect on Per capita Income. Meanwhile, investment has a positive and insignificant effect on per capita income. Simultaneously, the Population, Investment and Government Expenditure have a significant positive effect on the City and District Per capita Income in North Maluku Province in 2016-2020.